(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Domestic mites are the most remarkable cause of allergy in Italy. The most important species responsible of the fenomenon are Dermatophagoides pteronyssinus, D. farinae, Euroglyphus maynei, Acarus siro, Tyrophagus putrescentiae, Glycyphagus domesticus, Lepidoglyphus destructor and Gohieria fusca. The objects of this work were: 1) to evaluate the effect of conventional sanitary measures (use of detergents and household cleaning solutions) to create an environment poor in allergens through RAST inhibition; 2) to evaluate acaricide and denaturing activity of the most commonly used cleaning agents; 3) to evaluate the possibility of using essential oils in order to get rid of domestic mites. The most effective measures for the prevention of mites growth are: weekly change of sheets and pillow-cases, elimination of natural fibres carpeting, use of vacuum cleaner with HEPA filter. On the contrary, mites growth is favoured by double window-panes. Only anionic and non ionic, detergents caused high mortality in mite populations; all the cleaning products tested haven’t any denaturing activity. Among ten tested essential oils, the most effective ones resulted: caraway, garlic, black pepper and Peru balsam. Caraway oil was further analyzed in its main components, carvone and carvacrol. Caraway was later formulated at 1% with three detergents, saving its acaricidal activity. The essential oils combined with household cleaning solutions could help to reduce sensitization risk in domestic mites allergic subjects.